Kingella kingae Spinal Infections in Children - Eleftheria Samara; Nicolas Lutz; Pierre-Yves Zambelli (MDPI AG, 2022)
Nowadays, Kingella kingae is considered an important cause of primary spinal infections in children aged between 6 and 48 months. The presentation of the disease is often characterized by mild clinical features and a moderate biological inflammatory response, requiring a high index of suspicion. Performing magnetic resonance imaging (MRI) and obtaining an oropharyngeal specimen and subjecting it to a K. kingae-specific nucleic acid amplification test are recommended for its diagnosis. Most patients respond promptly to conservative treatment after administration of antibiotic therapy, which is prolonged for up to 3 months according to the individual clinical and biological response. Invasive surgical procedures are not required except for children who do not improve with antibiotic treatment, develop signs of cord compression, or if the presence of atypical microorganisms is suspected. Kingella kingae spinal infections usually run an indolent and benign clinical course, living no permanent sequelae.